STRATEGI PENANAMAN PENDIDIKAN KARAKTER BERKELANJUTAN PADA ANAK DI SEKOLAH - Haidir Lubis (Tazkiya: Jurnal Pendidikan Islam, 2016)
Planting character education is very important and urgent to be done to our children in school. Due to the fact that in the daily life of their children who are not characterized as violence, bullying, cheating on exams, lazy learning, of disobedience to parents and teachers, and others. It is important to do in the school given that older people with a wide range of busy work and career so memorable to instill character values in their children at home. Therefore schools should play an active role optimally to infuse the character education in the school learners in a sustainable manner. The strategies that can been made by four things, through: program of self-development, integration into all subjects, Penginetgrasian into co-curricular and extracurricular activities, and habituation. This is done in an effort to ensure the future of our children as immoral and degenerate generation in accordance with the values of Islam.Keywords: Strategy, character education, school.